Faktor-Faktor yang Memengaruhi Manajemen Laba pada Perusahaan Manufaktur di Indonesia - Kevin, Jun; Taufik, Haviz (https://jurnal.binamandiri.ac.id/, 2023)
This study aims to examine the significant effect of financial leverage, profitability, company size, managerial ownership, institutional ownership, and audit quality on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. A purposive sampling method was used to select 25 companies as a sample, with a total of 75 data. Data processing uses the SPSS 26 and data analysis uses a multiple linear regression model. The results showed that there was no significant effect of financial leverage, profitability, firm size, managerial ownership, institutional ownership, and audit quality on earnings management. Further research should involve other factors or broaden the scope of the industry to gain a deeper understanding of earnings management.